If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -1(3x + -9) = 57 Reorder the terms: 11x + -1(-9 + 3x) = 57 11x + (-9 * -1 + 3x * -1) = 57 11x + (9 + -3x) = 57 Reorder the terms: 9 + 11x + -3x = 57 Combine like terms: 11x + -3x = 8x 9 + 8x = 57 Solving 9 + 8x = 57 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 8x = 57 + -9 Combine like terms: 9 + -9 = 0 0 + 8x = 57 + -9 8x = 57 + -9 Combine like terms: 57 + -9 = 48 8x = 48 Divide each side by '8'. x = 6 Simplifying x = 6
| 8r+17=57 | | 8(67/4n)=10(44n+2) | | 6c-6=36 | | 36/32=n/8 | | W/2-6=-10 | | 8(67w/4n)=10(44n+2) | | 9m+11=29 | | 12=2+10(x-5) | | .50(-14)-3= | | 1.6(x+5)-(6.2+0.6x)=-3+2 | | (3-7i)(8+3i)=0 | | 2.96x+3.74=-3.48x-6.15 | | 11d+6=3 | | n-5+7=-4 | | 0.4/-20 | | 4x+9x-8x-5=10 | | 4(-7+x)=5x+(1/4) | | 9x-(5x-9)=5+3x | | 2-17=z/-9 | | -x+4=-20+x | | 3x^2-40x+36=0 | | b+7=7+2b-b | | 8x^2(9x^3-6x+7)= | | -n=-50 | | 4n-2n=16 | | .50(x)-3=-16 | | -3a+6+5a=7a | | Z^2-8z+12= | | 5y+1/4=4y-1/2 | | x/2=4/9 | | .50(x)-3=-14 | | 5/1=m/4 |